2013
DOI: 10.1105/tpc.113.110015
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Functional Maize Centromere after Loss of Centromeric Sequences and Gain of Ectopic Sequences

Abstract: The maize (Zea mays) B centromere is composed of B centromere-specific repeats (ZmBs), centromere-specific satellite repeats (CentC), and centromeric retrotransposons of maize (CRM). Here we describe a newly formed B centromere in maize, which has lost CentC sequences and has dramatically reduced CRM and ZmBs sequences, but still retains the molecular features of functional centromeres, such as CENH3, H2A phosphorylation at Thr-133, H3 phosphorylation at Ser-10, and Thr-3 immunostaining signals. This new centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 56 publications
2
69
0
3
Order By: Relevance
“…Another example was a newly formed B chromosome-centromere, which lacked maize centromeric sequence CentC and contained an extremely low content of CRM and B-repeat (B chromosome specific repeat) sequences. Immunostaining and other analysis also revealed the formation of a neocentromere, which was located on an 723 kb region of chromosome 9S [43]. Taken together, the results revealed that centromeric DNA sequences are not necessary for centromere formation.…”
Section: Centromere Identity Is Epigenetically Determinedsupporting
confidence: 55%
“…Another example was a newly formed B chromosome-centromere, which lacked maize centromeric sequence CentC and contained an extremely low content of CRM and B-repeat (B chromosome specific repeat) sequences. Immunostaining and other analysis also revealed the formation of a neocentromere, which was located on an 723 kb region of chromosome 9S [43]. Taken together, the results revealed that centromeric DNA sequences are not necessary for centromere formation.…”
Section: Centromere Identity Is Epigenetically Determinedsupporting
confidence: 55%
“…In contrast, normal maize centromeres, as noted above, are typically several megabases. The regular occurrence of de novo centromeres found here and previously (24,25) indicates that they are capable of being formed regularly on chromosomal fragments that are structurally acentric; however, they do not persist in normal chromosomes. The reason might reside in the previous observation in maize (30) and wheat (32) that in functional dicentrics the smaller centromere becomes inactive in a tug of war between large and small.…”
Section: Significancementioning
confidence: 78%
“…There are also de novo centromeres in human formed far from native centromeres (20). We have previously described two de novo centromeres in maize: one is near the position of the native centromere (25) and the other is distal to the site of the corresponding native centromere (24). Specific chromatin environments may be required for centromere formation, but the major elements are as yet unknown.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Neocentromere activation is usually associated with the loss of the original centromere (duSart et al 1997), or with inactivation but retention of the original centromere on the same chromosome (Amor et al 2004;Wang et al 2014). The vast majority of neocentromeres, including several plant neocentromeres (Nasuda et al 2005;Fu et al 2013;Wang et al 2014;Zhang et al 2013a), do not contain long arrays of satellite repeats that are typically associated with centromeres. The neocentromeric DNA sequences are generally deficient in genes, but otherwise not distinct from average genome sequences (Marshall et al 2008;Wang et al 2014).…”
mentioning
confidence: 99%